The confidential character of the relation of citizen to the agency responsible for the operational – search activity. (Journal of actual problems of jurisprudence, 2016)
This article addresses the issue of the confidential character of the relationship of citizens to the authorities responsible for the operational-search activity. The people of these citizens are called by different names: informants, snitches,informants, confidant, etc. However, in the world there is no law enforcement agency that can perform its tasks without these people. Also as well as in other states, characteristic of activity of operational search bodies and their employees in Kazakhstan is implementation of operational work by them with a support on support of citizens. Work confidentialassistants today lacks broad public support. It it is connected in many respects by that operational search activity often gains conflict character. In the process of doing the law allows violations of the rights protected by law and the interests of individuals and legal entities.
Keywords: confidentiality relations; operational-search activity; promotion; cooperation; confidential assistants